To the Study of the Rural District of the Golden Horde City of Ukek: Archaeological and Archaeozoological Research Results of the Shiroky Buerak Settlement in 2021 - Liliya V. Yavorskaya; Margarita A. Izotova; Olesya A. Kubankina (Нижневолжский археологический вестник, 2023)
The paper presents the results of archaeological and archaeozoological study of the 2021excavation material from the Shiroky Buerak settlement which is a part of the Golden Horde city of Ukek. The purpose of the study is to reconstruct a part of the economic functions of this settlement in the life support system of a larger town. The excavations revealed three stratigraphic horizons, remains of several service amenities outbuildings and pits. The ceramic complex is mainly represented by fragments of local production vessels: unglazed red-clay, red-brown, and ancient Russian gray-clay. Fragments of tandoors, coatings, as well as the production of unglazed red clay ceramics were found. However, no special buildings were identified. Other finds include iron, bronze, bone items typical material culture of an “ordinary” rural settlement remains. The coins allow dating the monument to the early 14th century. The archaeozoological collection included 444 fragments of bone remains of mammals, birds, fish, and reptiles which is typical for the rural settlements of this area according to the taxonomic set. The remains of sturgeons found in the cultural layers testify to the specialized fishing industry of the Volga region. The collection is dominated by domestic ungulates bones, among which the remains of cattle are of the highest proportion up to 70%. The proportions of the remains of small ruminants and horses are close to each other 15%and 13% respectively, while about 1% is presented by pig bones. Beef decisively dominates in the meat consumption of the settlement making up to 81%, which suggests that specialized breeding of cattle was one of the important aspects of economic activity to the detriment of other types of domestic ungulates breeding. A comprehensive archaeological and archaeozoological study revealed that the studied monument – Shiroky Buerak is a rural-type settlement with finds typical of the Ukek district, according to its industries, ceramic complex, and the residents` economic activities. The hypothesis about the important role of such settlements in supplying cities with meat products and provision of animal skins for processing by urban artisans has been confirmed, since such industries were found previously in the Ukek excavations.